Results from a state-based surveillance system for carbon monoxide poisoning. - Graber JM; Smith AE (Public Health Reports)
Objectives. The purpose of this study was to describe results from a pilot surveillance system for carbon monoxide poisoning--a significant yet prevent-able public health issue for which most public health agencies do not conduct routine public health surveillance.Methods. The authors developed a rate-based statewide surveillance system. Cases were identified using the 1998 Council of State and Territorial Epidemiologists' case definition in hospital discharges, emergency department and hospital outpatient visits, and mortality data. Intentional and fire-related injuries were excluded. The system was supplemented with qualitative information from newspaper articles. Annual, age, and sex-specific incidence rates were estimated. Exposure source/setting was described using E-codes; occupational setting was assessed by combining E-codes and payer code. Cases occurring during a disaster-related power outage in January 1998 were compared with cases identified during routine surveillance from 1999 through 2003.Results. During the five years of routine surveillance, 740 cases were identified; 47 (6.4%) were hospitalized, 442 (59.7%) were seen in an emergency department, and 251 (34.3%) were seen in another outpatient setting. More cases were observed in fall/winter; 23.1% of patients aged 16 or older were classified as exposed in an occupational setting. Among disaster-related cases, more were older (>/=65 years of age; 11.9% vs. 4.2%) and female (61.6% vs. 45.3%); and fewer were in occupational settings (1.8% vs. 23.1%).Conclusions. Establishing state-based public health surveillance for CO poisoning is feasible and essential for guiding prevention and control efforts. The finding that more than 20% of cases were classified as occupational should be investigated further.